1
$\begingroup$

I'm trying to show that $$ E[(Y- E[Y|X])(E[Y|X] - E[Y])] = 0. $$ My attempt is as follows: \begin{align*} & E[(Y- E[Y|X])(E[Y|X] - E[Y])] \\ &= E[YE[Y|X] - Y E[Y] - E[Y|X]^2 +E[Y|X]E[Y]]\\ &= E[YE[Y|X]] - E[Y E[Y]] - E[E[Y|X]^2] +E[E[Y|X]E[Y]]\\ &= E[E[Y|X]E[Y|X]] - E[E[Y|X] E[Y]]\\ &\qquad - E[E[Y|X]^2] +E[E[Y|X]E[Y]]\\ &= 0 \end{align*}

However, I seemed to have misused the law of iterated expectations when I set $$ E[YE[Y|X]] = E[E[Y|X]E[Y|X]]. $$ How can I justify this? Or is it just wrong?

$\endgroup$
1
$\begingroup$

Note that $E[Y\mid X]$ is $\sigma(X)$-measurable, hence $$ E[Y\mid X]^2 = E[YE[Y\mid X]\mid X] $$ giving $$ E \bigl[E [Y \mid X]^2\bigr] = E\bigl[ E[YE[Y\mid X]\mid X] \bigr] = E\bigl[YE[Y\mid X]\bigr]. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.